Regrouping of endowments in exchange markets with indivisible goods - Dinko Dimitrov; Claus-Jochen Haake (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
In this paper we are interested in efficient and individually rational exchange rules for markets with heterogeneous indivisible goods that exclude the possibility that an agent benefits by regrouping goods in her initial endowment. We present a suitable environment in which the existence of such rules can be analysed, and show the incompatibility of efficiency, individual rationality and regrouping-proofness even if agents' preferences are additive separable.
urn:nbn:de:hbz:361-7321
Keywords: C71; D71; D78; D82; H41; 330; Exchange markets; Indivisible goods; Regrouping-proofness